CASZ1 loss-of-function mutation associated with congenital heart disease - Huang, Ri-Tai; Xue, Song; Wang, Juan; Gu, Jian-Yun; Xu, Jia-Hong; Li, Yan-Jie; Li, Ning; Yang, Xiao-Xiao; Liu, Hua; Zhang, Xiao-Dong; Qu, Xin-Kai; Xu, Ying-Jia; et al. (Gene, 2016)
As the most common form of birth defect in humans, congenital heart disease (CHD) is associated with substantial morbidity and mortality in both children and adults. Increasing evidence demonstrates that genetic defects play a pivotal role in the pathogenesis of CHD. However, CHD is of great heterogeneity, and in an overwhelming majority of cases, the genetic determinants underpinning CHD remain elusive. In the present investigation, the coding exons and flanking introns of the CASZ1 gene, which codes for a zinc finger transcription factor essential for the cardiovascular morphogenesis, were sequenced in 172 unrelated patients with CHD. As a result, a novel heterozygous CASZ1 mutation, p.L38P, was identified in an index patient with congenital ventricular septal defect (VSD). Genetic scanning of the mutation carrier's available family members revealed that the mutation was present in all affected patients but absent in unaffected individuals. Analysis of the proband's pedigree showed that the mutation co-segregated with VSD, which was transmitted as an autosomal dominant trait with complete penetrance. The missense mutation, which altered the amino acid that was highly conserved evolutionarily, was absent in 200 unrelated, ethnically-matched healthy subjects used as controls. Functional deciphers by using a dual-luciferase reporter assay system unveiled that the mutant CASZ1 had significantly reduced transcriptional activity as compared with its wild-type counterpart. To the best of our knowledge, the current study firstly identifies CASZ1 as a new gene predisposing to CHD in humans, which provides novel insight into the molecular mechanisms underlying CHD and a potential therapeutic target for CASZ1-associated CHD, suggesting potential implications for personalized prophylaxis and therapy of CHD. •A CASZ1 mutation (p.L38P) was identified in a family with ventricular septal defect.•The mutation co-segregated with ventricular septal defect with complete penetrance.•The mutation was absent in 400 reference chromosomes.•The mutation was predicted to be disease-causing.•The mutant CASZ1 had significantly reduced transcriptional activity.